EFFICANCY OF GLIBENCLAMIDE FOR THE CONTROL OF GESTATIONAL DIABETES MELLITUS - Quddsia Tanveer; Anees Faima; Mubashra Naz (Journal of University Medical & Dental College, 2015)
ABSTRACT OBJECTIVE: To evaluate the efﬁcacy of glibenclamide for control of gestational diabetes mellitus. STUDY DESIGN: An interventional: Quasi-experimental PLACE AND DURATION OF STUDY: Study was carried out at Obstetrics & Gynaecology department of Punjab Medical College and afﬁliated hospital, Faisalabad. The study duration was six months from Apr 2008 to Sep 2008. MATERIAL AND METHOD: Total of 50 Patients with gestational diabetes mellitus (GDM) were treated with oral glibenclamide. Achievement of satisfactory glycemic control, maternal hypoglycemia, complications like macrosomia, neonatal hypoglycemia, hypocalcaemia, neonatal polycythemia, gross neonatal congenital anomalies, transient tachypnea of new born (TTN) and need for admission in neonatal intensive care unit were main outcome measures. RESULTS: Of the 50 patients treated with glibenclamide, 40 (80%) achieved satisfactory glucose control. Maternal hypoglycemic events were found in 1 (2%), macrosomia in 07(14%), neonatal hypoglycemia in 05(10%), transient tachypnea of newborn in 4(8%) and need for admission to neonatology in 09 (18%) of cases. No case of gross congenital abnormality, neonatal hypocalcaemia and neonatal polycythemia observed. SCONCLUSION: In treatment of GDM, glibenclamide is successful in achieving good glycemic control.